2019
DOI: 10.1093/treephys/tpz123
|View full text |Cite
|
Sign up to set email alerts
|

Propagating ice front induces gas bursts and ultrasonic acoustic emissions from freezing xylem

Abstract: Ice formation and propagation in the xylem of plants is a complex process. During freezing of xylem sap, gases dissolved in liquid sap are forced out of the ice lattice due to their low solubility in ice, and supersaturation of xylem sap as well as low water potential (Ѱ) are induced at the ice–liquid interface. Supersaturation of gases near the ice front may lead to bubble formation and potentially to cavitation and/or to burst of gases driven out from the branch. In this study, we investigated the origin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The bubbles also tended to be larger and less spherical, although this is only evident in fibers due to the lack of bubbles in the vessels of the saturated samples (Figure 5). These observations are consistent with previous studies that show significant gas bursts coming out from xylem during ice propagation (Lintunen et al, 2014, 2020). Together these results suggest that bark that is permeable to gases can decrease the risk of embolism formation in trees.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The bubbles also tended to be larger and less spherical, although this is only evident in fibers due to the lack of bubbles in the vessels of the saturated samples (Figure 5). These observations are consistent with previous studies that show significant gas bursts coming out from xylem during ice propagation (Lintunen et al, 2014, 2020). Together these results suggest that bark that is permeable to gases can decrease the risk of embolism formation in trees.…”
Section: Discussionsupporting
confidence: 94%
“…Based on these results and previous literature, we hypothesize that more, larger and less spherical bubbles are grown due to the low water potential in the remaining sap at the ice front, which locally increases tension in the sap, inducing the formation of large gas voids and acoustic emissions (Charrier et al, 2014, 2015). Previous studies have shown that the amount of acoustic emissions detected from freezing xylem is typically small for saturated samples and increase with increasing dehydration until the majority of the xylem gets embolized due to the prefreezing dehydration (Charrier et al, 2015; Lintunen et al, 2020; Mayr et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The air stream concentration was measured from both cuvettes every three minutes. See details of the measurement system in Lintunen et al (2020) . Surface area of the bark was calculated based on branch diameter measurement assuming a cylinder branch shape inside the cuvette with 5.5 cm inner length.…”
Section: Methodsmentioning
confidence: 99%